La “potenza del negativo” come destino dell’Europa: un libro di Biagio de Giovanni - Antonio Luongo (Democrazia e Diritti Sociali)
In this contribution we analyze the constitutive connection of Europe and philosophy in the thought of Biagio de Giovanni, within a properly ‘ontology’ field, according to a ‘fundamental speculative figure’ which is articulated in an ‘ontology of being of becoming’, perpetually activated by the ‘power of becoming’. Within this ‘original structure’, to quote Severino, the history of Europe manifests itself in the ‘figures’ of Athens, Jerusalem, Rome, up to the modern age and Hegel who represents the fulfillment of the reason-history relationship and the The beginning of its dissolution, with Marx and then with Nietzsche and Heidegger. The twentieth century then presents itself, on the one hand, as innervated by the ‘criminal metaphysics’ of totalitarianism and, on the other, by an extraordinary process of constitutionalisation and humanisation of democratic societies. The conclusion, thoughtful and dramatic, presents Europe suspended between a general condition of weakening and the need for a ‘great policy’ capable of giving it back a role in world history.